EVALUATION OF LEARNING OUTCOMES IN SOCIAL ARITHMETIC MATERIALS BY APPLYING THE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) COOPERATIVE LEARNING MODEL - Siti Mawaddah; Nailul Authary (Prodi Tadris Matematika Universitas Muhammadiyah Aceh, 2022)
The purpose of this study was to describe the evaluation of learning outcomes on the application of the student team achievement division (STAD) cooperative model to social arithmetic material for class VII MTsS Baitul Arqam. This study uses a quantitative method with a descriptive approach. This study's population was all class VII MTsS Baitul Arqam, while the sample consisted of 25 students. The instrument used was an arithmetic test question on STAD learning. After the data is obtained, then the data is analyzed with the percentage of completeness. The results of the study were based on the analysis of the data on the results of the learning completeness of class VII students of MTsS Baitul Arqam on the social arithmetic material above; the result was found that 100% of students in class VII had completed learning activities using the STAD type cooperative learning model. Therefore, it can be stated that the learning outcomes of class VII students of MTsS Baitul Arqam on social arithmetic material in a classical manner have been completed with 100% completeness.